The athletic skills model - optimizing talent development through movement education - Wormhoudt, R.; Savelsbergh, G. J. P.; Teunissen, J. W.; Davids, K. (Routledge, 2018)
The Athletic Skills Model offers an alternative to dominant talent development theories in the form of holistic broad-based movement education, focusing on health and wellbeing. It places the emphasis on `physical intelligence` - including attributes such as agility, flexibility and stability - through adaptable and varied training programmes, creating a skilled athlete before introducing sport specialization.